2018
DOI: 10.28986/jtaken.v4i2.218
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Intention on Whistleblowing: An Analysis on Moderated Model of Whistleblowing Channel

Abstract: The purpose of this study is to examine and provide empirical evidence of the effect of personal responsibility, personal cost and education on whistleblowing intention, as well as the impact of whistleblowing channel in influencing personal cost on whistleblowing intention. The populations of this study are civil servants (ASN) from financial department and procurement services department in Banjarmasin Municipal Government. The sample of this study are 104 respondents, obtained using saturated sampling techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
1
3
0
2
Order By: Relevance
“…To become a whistleblower requires various considerations, not only having a good personality, but environmental conditions and security as well as thinking about one's own fate and the fate of the organization if something bad happens and has a negative impact on promotion for the institution. This finding is consistent with [51] who found that civil servants consider their personal responsibility when they intend to leak secrets. Locus of control has a significant positive effect on the intention not to carry out whistleblowing [52].…”
Section: Hypothesis Testsupporting
confidence: 91%
“…To become a whistleblower requires various considerations, not only having a good personality, but environmental conditions and security as well as thinking about one's own fate and the fate of the organization if something bad happens and has a negative impact on promotion for the institution. This finding is consistent with [51] who found that civil servants consider their personal responsibility when they intend to leak secrets. Locus of control has a significant positive effect on the intention not to carry out whistleblowing [52].…”
Section: Hypothesis Testsupporting
confidence: 91%
“…This is what is generally considered a personal cost (Schultz et al, 1993). Fear of reprisal/retaliation is a significant factor influencing the intention to report fraud Iskandar & Saragih (2018), If management's attitude towards whistleblowers proves to be indifferent, hostile, and even hateful, then this will force individuals to be rational by only being inactive observers (Putriana et al, 2018).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Maka, peran dari perguruan tinggi sangat besar dalam menciptakan suasana pembelajaran bagi unsur-unsur didalamnya. Individu akan mengamati lingkungan sebagai bagian yang tidak terpisahkan dari diri mereka dan mampu mendorong terciptanya lingkungan kerja yang etis (Putriana et al, 2018) dan dalam konteks keputusan investasi, kecerdasan spiritual juga terhubung dengan logika yang serupa yakni kecerdasan spiritual dibangun dari penciptaan suasana pembelajaran sosial dalam hal ini adalah Perguruan Tinggi.…”
Section: Pengaruh Narsisme Terhadap Perilaku Keputusan Investasi Deng...unclassified